Penyuluhan Edukasi Pentingnya Pemberian ASI Eksklusif Bagi Ibu dan Anak Pada Kegiatan Kampung ASI di Kelurahan Balongsari Kota Surabaya - Hutabarat, Agnes; Elvandari, Milliyantri; Cahyani, Tutik (Journal Of Human And Education (JAHE), 2024)
Breastfeeding failure is still common among mothers who are unable to exclusively breastfeed their children. Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%. Breast milk plays an important role in the survival of infants. Overcoming the problem of low exclusive breastfeeding coverage requires the participation of many parties. One of the efforts of the Surabaya City government is the establishment of Kampung ASI. This community service activity uses community education methods in the form of counseling, mentoring, lectures, questions and answers, and practices with material presented related to the importance of exclusive breastfeeding for the health of mothers and children. The implementation of this counseling was carried out using printed visual media, namely leaflets as educational tools. The targets of this activity are the community, especially pregnant women, mothers of infants and toddlers aged 0-2 years, and breastfeeding companion cadres in the Balongsari Village area. Providing exclusive breastfeeding counseling at the age of 0-6 months in Kampung ASI is intended to spread awareness about the benefits of exclusive breastfeeding and foster confidence in working mothers to provide exclusive breastfeeding optimally in the first 6 months of a baby's life. This approach not only educates parents, but also encourages them to exclusively breastfeed their babies.